ANALISIS FAKTOR-FAKTOR PENENTU KECURANGAN (FRAUD) PADA SEKTOR PEMERINTAHAN (STUDI KASUS PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA PEKALONGAN) - Moh. Risqi Kurnia Adi; Komala Ardiyani; Arum Ardianingsih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2016)
THE PERCEPTION OF AN INCREASE IN ACCOUNTABILITY AND TRANSPARENCY OF THE GOVERNMENT SECTOR, ESPECIALLY FOR EMPLOYEES SHOULD BE CARRIED OUT CONTINUOUSLY. THIS STUDY AIMS TO PROVIDE EMPIRICAL EVIDENCE THAT LAW ENFORCEMENT, THE EFFECTIVENESS OF INTERNAL CONTROL, INFORMATION ASYMMETRIES, COMPLIANCE COMPENSATION, PROCEDURAL JUSTICE, ORGANIZATIONAL ETHICAL CULTURE, ORGANIZATIONAL COMMITMENT EFFECT ON FRAUD. METHODS OF DATA COLLECTION IS DONE BY PURPOSIVE SAMPLING AND EARNED THIRTY-FIVE (35) RESPONDENTS. THE DATA USED ARE PRIMARY DATA. MECHANICAL ANALYSIS INCLUDES TESTING THE QUALITY OF THE DATA AND THE CLASSICAL ASSUMPTION TEST AND MULTIPLE LINEAR REGRESSION ANALYSIS WITH T TEST AND F TEST RESULTS SHOWED THAT ALL VARIABLES TESTED SIMULTANEOUSLY CAPABLE OF AFFECTING CHEATING. PARTIALLY, INFORMATION ASYMMETRY AND ORGANIZATIONAL COMMITMENT SIGNIFICANT EFFECT ON FRAUD (FRAUD). WHILE SIMULTANEOUSLY ENFORCEMENT, INTERNAL EFFECTIVENESS, APPROPRIATENESS OF COMPENSATION, PROCEDURAL FAIRNESS, AND ETHICAL INFLUENCE THE ORGANIZATION HAS NO SIGNIFICANT EFFECT AGAINST FRAUD (FRAUD).